2019
DOI: 10.28945/4452
|View full text |Cite
|
Sign up to set email alerts
|

Assessing ESL Learners’ Online Learning Self-Efficacy in Thailand: Are They Ready?

Abstract: Aim/Purpose: The purpose of this study was to examine whether ESL students in Thailand felt comfortable and confident using online course management tools as indicated by the levels of their online learning self-efficacy. Background: While online learning has become commonplace in most US based universities, some international educational institutions are just now dealing with the enormous task of introducing online learning to their academic communities and working with both faculty and students for successf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 29 publications
2
17
0
Order By: Relevance
“…Similar results from studies on online learning during the pandemic have been reported by Chen et al (2021) in China, Fachmi, Alsolami, Sopacua, andPrajogo (2021) in Indonesia, and Lin (2021) in Taiwan. Higher self-efficacy leading to higher satisfaction with online learning was also reported by pre-pandemic studies conducted by Joo, Lim, and Kim (2013) in Korea, Artino (2008); Wang, Shannon, and Ross (2013) and Zimmerman and Kulikowich (2016) in the U.S., and Ramsin and Mayall (2019) in Thailand.…”
Section: Discussionsupporting
confidence: 61%
“…Similar results from studies on online learning during the pandemic have been reported by Chen et al (2021) in China, Fachmi, Alsolami, Sopacua, andPrajogo (2021) in Indonesia, and Lin (2021) in Taiwan. Higher self-efficacy leading to higher satisfaction with online learning was also reported by pre-pandemic studies conducted by Joo, Lim, and Kim (2013) in Korea, Artino (2008); Wang, Shannon, and Ross (2013) and Zimmerman and Kulikowich (2016) in the U.S., and Ramsin and Mayall (2019) in Thailand.…”
Section: Discussionsupporting
confidence: 61%
“…Online learning in the ESL classroom exposes students to new pedagogical innovations with the aid of technology which allows quick mastery of language skills and increased students' motivation and excitement (Mohamad, Ghazali & Hashim, 2018). ESL learners can search and retrieve a wide variety of learning resources that are accessible online without limits (Ramsin & Mayall, 2019). This is an advantage for ESL learners especially in the 21 st century whereby the focus of language learning is no longer entirely on grammar but rather the ability of the learners to practice the language proficiently and effectively (Ramsin & Mayall, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…ESL learners can search and retrieve a wide variety of learning resources that are accessible online without limits (Ramsin & Mayall, 2019). This is an advantage for ESL learners especially in the 21 st century whereby the focus of language learning is no longer entirely on grammar but rather the ability of the learners to practice the language proficiently and effectively (Ramsin & Mayall, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations